Measurement of the top quark mass and pp̄→tt̄ cross section in the all-hadronic mode with the CDF II detector - Aaltonen, T; Adelman, J; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; et al. (2010)
We present a measurement of the top quark mass and of the top-antitop (tt̄) pair production cross section using pp̄ data collected with the CDF II detector at the Tevatron Collider at the Fermi National Accelerator Laboratory and corresponding to an integrated luminosity of 2.9fb-1. We select events with six or more jets satisfying a number of kinematical requirements imposed by means of a neural-network algorithm. At least one of these jets must originate from a b quark, as identified by the reconstruction of a secondary vertex inside the jet. The mass measurement is based on a likelihood fit incorporating reconstructed mass distributions representative of signal and background, where the absolute jet energy scale (JES) is measured simultaneously with the top quark mass. The measurement yields a value of 174.8±2.4(stat+JES)-1.0+1.2(syst)GeV/c2, where the uncertainty from the absolute jet energy scale is evaluated together with the statistical uncertainty. The procedure also measures the amount of signal from which we derive a cross section, σtt̄=7.2±0.5(stat)±1.0(syst) ±0.4(lum)pb, for the measured values of top quark mass and JES. © 2010 The American Physical Society.